Writing suburbia: the periphery in novels (2013)
Perhaps somewhat befi tting their positioning vis-a-vis the city, the suburbs still manage to be comparatively marginalized in overview considerations of fi ction. Th ere is a Penguin Book of the City ; an anthology of fi ctional writing capturing stories spun in the metropolis. Presumably due to its perceived naff ness, there is no equivalent volume dealing with the suburb. Yet the examples of such work are voluminous and vary vastly. At one extreme the futuristic Neuromancer by William Gibson ( 1984 ) which contains the fi rst ever mention of the word ‘cyberspace’ describes a postsuburban ‘edge city’ (cf. Garreau) environment where business and technology are emeshed with multinational corporations in a sprawl called BAMA, the Boston–Atlanta Metropolitan Axis in which the entire American East Coast from Boston to Atlanta, have merged into a single urban mass. At the other extreme of suburban fi ction can be found the historical sweep of events and moralistic undertone of the Delderfi eld ‘Avenue’ books set from 1919 to 1940.